Xylose production of oil palm frond using dilute acid hydrolysis - Amirkhani, Hadi (2013)
Oil Palm Frond (OPF) is a lignocellulosic waste from palm oil plantation. This study focuses on the first part of the two-stage dilute acid hydrolysis of OPF fiber namely the conversion of hemicellulose to simple sugar (xylose as a type of pentose sugar).The characterisation of OPF was accomplished by using thermogravimetric analysis (TGA) and fiber analysis to determine cellulose, hemicellulose and lignin. The hydrolysis process was conducted in a batch reactor. The experimental began with acid screening to select the most effective acid for OPF hydrolysis. Sulphuric acid (H2SO4), hydrochloric acid (HCl) and acetic acid (CH3COOH) were chosen as the potential catalysts and the acid hydrolysis was done at 100oC, solid to liquid ratio of 25:1 (w/v) and 2% (v/v) concentration of acid. Consequently,H2SO4 was found to yield the highest amount of xylose. The effect of the solid to liquid ratio (SLR) was then studied using 2% sulphuric acid by varying the ratio from 1:20 to 1:35 (w/v) at100oC. The ratio 1:30 gave the highest amount of xylose, hence it was chosen as an optimum solid to liquid ratio for subsequent experiments. The optimization study was conducted on acid hydrolysis of OPF fiber using sulphuric acid at SLR of 1:30. The manipulated reaction conditions were temperatures (100-140oC), acid concentrations (2-6%) and reaction times (0-240 min). The analysis of three monosugars namely xylose (main mono-sugar),glucose and arabinose as well furfural as inhibitor were determined using high performance liquid chromatography (HPLC). Based on the potential amount of xylose (10.8mg/ml), 94% conversion was obtained under the optimum conditions. This optimum yield was achieved at 2% (v/v) acid concentration, at 120oC in 120 minutes. The possibility of improving the hydrolysis OPF using ultrasound-assisted pre-treatment of OPF fiber was also investigated. The effects of ultrasonic power (40, 60, and 80%of 300 Watt) and irradiation time (20,30, 40, and 60min) were examined. After ultrasonic pre-treatment, thefibers were subjected to hydrolysis conducted at optimum conditions of hydrolysis process (2% acid sulphuric, 120oC and 120 minutes). The maximum yield of xylose at 7.31 mg/ml was achieved at 80% power after 40 minutes of ultrasonication. The yield was lower than the hydrolysis without pre-treatment because most of the sugar was degraded to furfural. The amount of furfural rose from 0.0163 mg/ml to 0.063 mg/ml after pre-treatment at optimum condition. The kinetics study on the dilute acid hydrolysis of OPFfiber revealed that the hydrolysis reaction is a first order irreversible reaction. Dilute acid hydrolysis reaction was analyzed using kinetics models developed by Saeman. Kinetics constants for Saeman model were analyzed using Arrhenius type expansion which includes activation energy and catalyst concentration factors.